Design, synthesis, and identification of silicon incorporated oxazolidinone antibiotics with improved brain exposure - Seetharamsingh, B.; Ramesh, Remya; Dange, Santoshkumar S.; Khairnar, Pankaj V.; Singhal, Smita; Upadhyay, Dilip; Veeraraghavan, Sridhar; Viswanadha, Srikant; Vakkalanka, Swaroop; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
Therapeutic options for brain infections caused by pathogens with a reduced sensitivity to drugs are limited. Recent reports on the potential use of linezolid in treating brain infections prompted us to design novel compounds around this scaffold. Herein, we describe the design and synthesis of various oxazolidinone antibiotics with the incorporation of silicon. Our findings in preclinical species suggest that silicon incorporation is highly useful in improving brain exposures. Interestingly, three compounds from this series demonstrated up to a 30-fold higher brain/plasma ratio when compared to linezolid thereby indicating their therapeutic potential in brain associated disorders.
Keywords: Antibacterial; brain exposure; linezolid; oxazolidinone; sila analogue

First total synthesis of gliomasolide C and formal total synthesis of sch-725674 - Seetharamsingh, B.; Khairnar, Pankaj V.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2016)
Syntheses of two 14-membered macrolides Sch-725674 and Gliomasolide C are described here. The first total synthesis of Gliomasolide C, the short synthesis of Sch-725674, and regios elective Wacker oxidation of internal olefin are the highlights of this disclosure. In addition, a key macrocyde with orthogonal functionalities was designed and synthesized on a gram scale for the generation of analogues.

Identification and synthesis of mycalol analogues with improved potency against anaplastic thyroid carcinonia cell lines - Cutignano, Adele; Seetharamsingh, B.; D'Angelo, Daniela; Nuzzo, Genoveffa; Khairnar, Pankaj V.; Fusco, Alfredo; Reddy, D. Srinivasa; Fontana, Angelo (Journal of Natural Products, 2017)
The marine metabolite mycalol (1) has a specific inhibitory activity on cells of anaplastic thyroid carcinoma (ATC), a very aggressive and rare cancer that does not have effective conventional therapy. In this study, we describe six new related analogues (2-7) that differ in the length of the terminal alkyl residue and the presence of acetate or 3S-hydroxybutyrate (3S)-3HB as a substituent at C-19. Despite the structural' analogies, some of the new members were significantly more-cytotokic than 1 on cell lines,derivecl from human ATC. Structures inclusive of the 2'R,3R,4S,7R,8S,19R absolute configuration were asigned to 2-7 on the basis of detailed spectroscopic analysis, synthesis of different isomers, and application of ECD and Mosher's methods. This work led to the identification of mycal61-578 (3) as the most potent analogue, with an IC50 of 2.3 mu M on FRO cells: